A new and exceptional species of Bradya Boeck, 1873 (Copepoda: Harpacticoida:Ectinosomatidae) from the abyssal plain of the Angola Basin and the variabilityof deep-sea Harpacticoida - Seifried, Sybille; Arbizu, Pedro Martínez (Zootaxa, 2008)
Bradya kurtschminkei sp. nov. is described from deep-sea samples collected from the Angola Basin (Southeast Atlantic) during the DIVA 1 campaign in 2000, the Guinea and Cape Basins (Southeast Atlantic) during the DIVA 2 campaign in 2005, and the Porcupine Abyssal Plain (Northeast Atlantic) during the RRS ‘‘Challenger’’ cruise 111 in 1994. B. kurtschminkei sp. nov. is exceptional because of many characters, hitherto unknown from other Bradya species. B. kurtschminkei sp. nov. can be distinguished from its congeners by its unique habitus as the body is slightly flattened dorso-ventrally and the female cephalothorax is almost as long as the free pedigerous somites and the urosome together. The rostrum’s length is a third of the cephalothorax length and it tapers to a point. The antennule is 5-segmented, the basis of maxillule is fused with exopod and endopod, and the endopod has only four setae. The endopod of maxilla has only one large claw, the exopod of the P5 is short, its distal end reaches to the distal end of the baseoendopod, and the outer seta of the baseoendopod has a double tip. The armature formula of P1–P4 is exceptional as there are in total seven setae less on the endopods than in all other species of Bradya. Like many other deep-sea Harpacticoida, B. kurtschminkei sp. nov. shows compared with shallow waters species a remarkable, as yet unknown morphological variability.